2013
DOI: 10.7466/jkhma.2013.31.4.113
|View full text |Cite
|
Sign up to set email alerts
|

Development of Korea Family Strengths Scale(KFSS-II)

Abstract: Exploratory factor analysis of 29 items extracted 5 factors. It included the 5 dimensional constructs of family resilience, valuing each other & acceptance, qualitative bonding, economic stability and cooperation and caring about community. Confirmatory factor analysis confirmed the stepwise 5-factor model of 22 items considering family strengths. These results indicated that the simple template of Family Strengths Scale would be a concise and reliable tool for assessing and evaluating a family's strengths.¯¯¯… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 6 publications
0
10
0
3
Order By: Relevance
“…(Otto, 1962) Strong Families (Stinnett & DeFrain, 1985) Healthy Families (Curran, 1983 The qualities of strong families have been used to develop scales to measure the presence of the traits and characteristics of strong families. These include, in the order in which they were developed, the Family Strengths Questionnaire (Otto, 1975), Family Strengths Inventory (Stinnett & DeFrain, 1985), Family Functioning Style Scale , Australian Inventory of Family Strengths (Silberberg, 2001), American Inventory of Family Strengths (DeFrain & Stinnett, 2002a), and Korea Family Strengths Scale (Yoo, Lee, Kim, & Choi, 2013). A literature search for studies using these scale to measure family strengths where strengths were empirically related to personal, family, and child well-being found, with only one exception (Arshat & Baharudin, 2014), that the majority of studies of the relationships between family strengths and well-being used the Family Functioning Style Scale (FFSS) to measure family strengths.…”
Section: Qualities Of Strong Familiesmentioning
confidence: 99%
“…(Otto, 1962) Strong Families (Stinnett & DeFrain, 1985) Healthy Families (Curran, 1983 The qualities of strong families have been used to develop scales to measure the presence of the traits and characteristics of strong families. These include, in the order in which they were developed, the Family Strengths Questionnaire (Otto, 1975), Family Strengths Inventory (Stinnett & DeFrain, 1985), Family Functioning Style Scale , Australian Inventory of Family Strengths (Silberberg, 2001), American Inventory of Family Strengths (DeFrain & Stinnett, 2002a), and Korea Family Strengths Scale (Yoo, Lee, Kim, & Choi, 2013). A literature search for studies using these scale to measure family strengths where strengths were empirically related to personal, family, and child well-being found, with only one exception (Arshat & Baharudin, 2014), that the majority of studies of the relationships between family strengths and well-being used the Family Functioning Style Scale (FFSS) to measure family strengths.…”
Section: Qualities Of Strong Familiesmentioning
confidence: 99%
“…Higher scores indicate greater family strength. For internal consistency reliability, Cronbach's ⍺ was .94 at the time of its development [13] and .95 in this study.…”
Section: Instruments 1) Family Strengthmentioning
confidence: 47%
“…A healthy family is characterized by mutual respect and acceptance, qualitative bonding, economic stability and cooper-ation, family elasticity, and family cultural and social participation [13]. This study found that family strength was associated with high economic status and self-perceived health.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations